2021
DOI: 10.1111/ene.14871
|View full text |Cite
|
Sign up to set email alerts
|

Novel noninvasive biomarkers of prodromal Alzheimer disease: The role of optical coherence tomography and optical coherence tomography–angiography

Abstract: Background and purpose A reduction of retinal thickness and an alteration of retinal perfusion have been found in Alzheimer disease (AD). Nowadays, retinal layers and retinal perfusion can be evaluated by means of noninvasive imaging techniques, namely, optical coherence tomography (OCT) and OCT‐angiography (OCT‐A). Here, we have compared the retinal thickness and the perfusion index, measured by means of OCT and OCT‐A, in patients with mild cognitive impairment due to AD (MCI‐AD) and in age‐ and sex‐matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…First, van de Kreeke et al reported a significantly higher VD in both peripapillary and macular regions in 13 Aβ + compared to 111 Aβ- cognitively healthy twins, but no differences in the FAZ size 23 . Biscetti et al showed higher measures of fractal dimension in a group of 24 MCI with a CSF AD-profile compared to a group of 13 controls 24 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, van de Kreeke et al reported a significantly higher VD in both peripapillary and macular regions in 13 Aβ + compared to 111 Aβ- cognitively healthy twins, but no differences in the FAZ size 23 . Biscetti et al showed higher measures of fractal dimension in a group of 24 MCI with a CSF AD-profile compared to a group of 13 controls 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Jiang et al showed similar results in a cohort of 12 ADD patients, 19 MCI patients and 21 controls 17 . Biscetti et al showed a significant reduction in both vascular perfusion density and vessel length density in a group of 24 MCI with a CSF AD-profile compared to a group of 13 controls 24 . Querques et al used dynamic vessel analyzer in a cohort of ADD, MCI and controls, and showed that the retinal neurovascular coupling was significantly impaired in ADD and MCI compared to controls 18 .…”
Section: Discussionmentioning
confidence: 98%
“…The link between these two apparently different conditions is further reinforced by the common finding of RNFL/GCL thinning and visual gray and white matters morpho-functional impairments (Iseri et al, 2006;Tamura et al, 2006;Ascaso et al, 2014;Jones-Odeh and Hammond, 2015). The relationship between retinal and CNS alterations is strong and support the role of OCT-based technology for the early diagnosis of cognitive dysfunctions and neurodegenerative diseases (Biscetti et al, 2021). A well-known glaucoma-related finding is the thinning of the lamina cribrosa, a complex tissue surrounding the ONH and providing structural and functional supports to the ganglion cells.…”
Section: Cognitive Impairment In Glaucomamentioning
confidence: 89%
“…In particular, the retina is considered a "window into the brain" and can be accessed noninvasively through optical coherence tomography (OCT), which is a fast, inexpensive, non-invasive and widely accessible tool used for the diagnosis and monitoring of common ocular pathologies (Jaffe and Caprioli, 2004). The study of retinal biomarkers for AD started with the analysis of structural parameters (e.g., thickness and volume of the different retinal layers in the peripapillary and macular regions) and more recently, investigators have focused on the study of the retinal microvasculature [e.g., vessel density (VD) and size of the foveal avascular zone, mainly] (Jiang et al, 2018;Querques et al, 2019;Wu et al, 2020;Biscetti et al, 2021). Besides, the retinal microvascular network can be directly assessed in vivo using high-resolution OCT-angiography (OCT-A), while this cannot be done for cerebrovascular disease with brain imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, OCT-A measures in the retina could be used as a proxy of brain vascular changes. Several publications have demonstrated abnormalities in retinal vascular parameters in AD and MCI patients compared to healthy controls, such as increases in the foveal avascular zone (FAZ) and decreases in VD (Cheung et al, 2014;Grewal et al, 2018;Jiang et al, 2018;Querques et al, 2019;Zabel et al, 2019;Zhang et al, 2019;Wu et al, 2020;Biscetti et al, 2021;Chalkias et al, 2021;Rifai et al, 2021), pointing to retinal vascular loss. The majority of cohorts reported in the literature, though, were relatively small and the results have not been validated in larger studies.…”
Section: Introductionmentioning
confidence: 99%